Subjects with temporomandibular joint disc displacement and body posture assessment via rasterstereography: a pilot case-control study - Di Paolo, C; Papi, P; Falisi, G; Pompa, G; Santilli, V; Polimeni, A; Fiorini, A (European review for medical and pharmacological sciences, 2020)
The possible relationship between temporomandibular disorders (TMDs) and body posture is still controversial. Rasterstereography has been introduced as a radiation-free, reliable and non-invasive method to analyze three-dimensional spinal posture. The aim of this case-control study is to evaluate, through rasterstereography, body posture parameters in a group of patients with reducible unilateral dislocation of the articular disc, compared to healthy volunteers. Rasterstereographic recordings obtained were compared between the two groups with a paired t-student test. Furthermore, the relationship between Rasterstereographic recordings and clinical data in the TMD group were analyzed by means of multiple regression analysis. Only lateral deviation was statistically significant different between the two groups (rms VPDM Control group 40% > TMD group, p=0.02; 43% control group VPDM max > TMD group, p<0.02). In the TMD group, a significant relationship (p<0.05) was found out between lateral and rotational deviations of the column and muscular pain, therefore suggesting a possible overactivity of the masticatory muscles, especially of lateral pterygoids' bilaterally and the left masseter. Patients with reducible unilateral disc displacement showed limited postural alterations compared to healthy volunteers, only lateral deviations (VPDM rms and VPDM-max) were statistically significant (Œ <0.05) between the two groups.